Analyzing the factors affecting reading literacy skills: The case of internal and external factors - Susanti, Marnis; Sukma, Elfia; Muhammadi; Gistituati, Nurhizrah (Universitas Jambi, Indonesia, 2025)
This research aimed to explain, analyze, and interpret the factors affecting the reading literacy skills of the fifth-grade students. This research used a mixed methods study. Data collection was carried out by direct observations, interviews, and minimum competency tests. In addition, the data analysis methods used in this research were data reduction, data presentation, and verification/conclusion. The results showed that reading literacy was influenced by internal factors (low intelligence ability, low interest in learning, and low learning motivation) and external factors (lack of parental attention, influence of TV and cell phones, influence of playmates, lack of teacher ability, and limited facilities and infrastructure). Efforts that can be made to overcome students' low reading literacy skills include providing motivation, literacy activities, increasing teacher abilities, exceptional guidance, collaboration with parents, and utilization of infrastructure.